REVIEW ON EFFECTS OF NITROGEN AND PHOSPHORUS FERTILIZERS RATES ON YIELD RELATED COMPONENTS AND YIELD OF POTATO (SOLANUM TUBEROSUM L.) - Ashwini A (African Journal of Environmental Economics and Management, 2024)
Potato (Solanum tuberosum L.) is one of the most important food crops in the world. It is ranked in fourth following wheat, maize and rice. It is very important food and cash crop in Ethiopia. Potato can give great emphasis’s as it gives highest nourishment per hectare. Absence of high yield and adaptable varieties, high susceptibility of the existing varieties for bacteria disease and poor tuber quality are the major production constraints in the area. Nitrogen and phosphorus management are perhaps the most important aspects of successful. Potato (Solanum tuberosum L.) Nitrogen and phosphorus fertilizers are applied in the form of P2O5, it is genetic potential for both nitrogen and phosphorus are important for vegetative and reproductive of potato. The main objective of this seminar is to review the effects of nitrogen and phosphorus fertilizers rates on yield related components and yield of potato (Solanum tuberosum L). Keywords: , , v